Learning through audio-visual aids: how does it work for students to delve into the English vowels? - Zikril Mulia (Erudita: Journal of English Language Teaching, 2022)
The research aims to investigate best and effective learning media to delve into the English vowels which is hard to be learnt in EFL classrooms. The research employed a descriptive qualitative approach with interview study which was to recognize the learning activities from participants. The participants of the research were five seventh-term university students of English department in South Sumatera, Indonesia. Data were garnered through observation and interview. The data were analyzed by conceptual analysis of empirical material and grounded theory. Findings of the research reveal that the five college students had difficulties in learning English vowels through the written material and listening. They were interested in enhancing the English vowels subject through audio-visual aids. Another result portrays that the university students met their needs and realized that learning through audio visual aids was such effective learning media. Visual aids assisted them to delve into the English vowels concisely, instead of listening and paid attention to the teacher during their English class. This study concludes with empirical evidence on how students deal with their learning experiences via audio-visual aids.